THE ETHICS OF HUMAN EMBRYONIC STEM CELL RESEARCH: PROPOSALS FOR A LEGAL FRAMEWORK FOR INDIA - Davis, J Charles (Asian Horizons, 2012)
India permits and promotes human embryonic stem cell research. India is also an embryo-surplus nation due to the widespread application of in-vitro-fertilization technology. Because of the high social value placed on progeny in India, many infertile couples avail this technology to get a child and thus escape from social ostracism. In the process, surplus embryos are produced. In the natural course, the surplus embryos would die and be discarded after a certain period of time when they have no chance to be implanted into the womb of a woman. Scientists want to use these surplus embryos for research and this demand is getting momentum all over the world. India permits human embryonic stem cell (hESC) research with surplus embryos up to 14 days old. The Guidelines on Stem Cell Research and Therapy by the Department of Biotechnology and Indian Council of Medical Research (DBT-ICMR Guidelines) regulate the whole field of stem cell research in India in the absence of a binding legislation. Governmental and private stem cell centres are to be approved by the Institutional Committees for Stem Cell Research and Therapy (IC-SCRT) and the Drug Control General of India (DCGI) and are to be registered under the National Committee for Stem Cell Research and Therapy (NAC-SCRT).